2001
DOI: 10.2169/internalmedicine.40.510
|View full text |Cite
|
Sign up to set email alerts
|

Three Patients with Isolated Adrenocorticotropin Deficiency Presenting with Neuroleptic Malignant Syndrome-like Symptoms.

Abstract: Wereport 3 patients with isolated adrenocorticotropin (ACTH)deficiency presenting with neuroleptic malignant syndrome (NMS)-like symptoms. All patients were in their 60's or 70's and showed consciousness disturbance, a highgrade fever, extrapyramydal signs, and muscle enzymeelevations, which met the criteria for NMS.Also, they all showed hyponatremia induced by isolated ACTHdeficiency. In addition to the standard therapy for NMS,corticosteroid supplement therapy was effective in all patients. There thus appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Regardless of clinical alertness, it might not be easy to differentiate NMS from a case of, for example, adrenocorticotropic hormone (ACTH) deficiency. Patients with ACTH deficiency can manifest a clinical picture very similar to that of NMS 110,111…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Regardless of clinical alertness, it might not be easy to differentiate NMS from a case of, for example, adrenocorticotropic hormone (ACTH) deficiency. Patients with ACTH deficiency can manifest a clinical picture very similar to that of NMS 110,111…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Hyponatremia has also been documented in association with neuroleptic malignant syndrome. [87][88][89][90] In fact, some authors have suggested that hyponatremia could act as precipitating factor for the development of this syndrome. [89][90] and ACTH deficiency 87 have been proposed to explain the hyponatremia in these patients.…”
Section: Hyponatremia In Other Neurologic Conditionsmentioning
confidence: 99%
“…Several cases of NMS accompanied by adrenal insufficiency have been reported [ 20 , 21 ]. Those patients easily recovered from NMS in response to corticosteroid supplementation.…”
Section: Discussionmentioning
confidence: 99%